Live Coding and Music Production as Hybrid Practice. - Boon, Hussein (Organised Sound, 2023)
This article discusses incorporating live coding as part of a new Foundation pathway for music production at a UK university that started in September 2022. The inclusion of live coding, using the application Sonic Pi, is situated alongside music production using a DAW, initially through the process of drum programming. The role of Sonic Pi is also to provide a means for producers to take their productions into the live performance space. This article's contribution is in three areas. The first is to provide a short history of live coding at the current institution coupled with a longer account of my fragmented journey into live coding to provide some context. For the second discussion area, information about the foundation, its structure and how it fits into the overall degree programme is discussed. This section also includes some short code examples to illustrate the approach and links to video materials. For the last discussion area I outline an area of crossover between production and live coding which opens up a number of critical discussion points. This concerns the use of a breakbeat, what this means when used in productions, in live coding and when shipped with paid for or free software.